Goitre Prevalence and Urinary Iodine Concentration in School-Aged Children in the Ashanti Region of Ghana - Daniel Gyamfi; Yaw Amo Wiafe; Enoch Ofori Awuah; Evans Asamoah Adu; Emmanuel Kodie Boadi (International Journal of Endocrinology)
Background. Iodine deficiency is a public health problem. The universal salt iodization (USI) program is the main, simple, and cost-effective intervention strategy to control iodine deficiency. The study examined the iodine status in school-aged children in Ashanti region, Ghana, using thyroid volumes along with urinary iodine concentrations, the methods recommended by the WHO/ICCIDD for monitoring the sustained impact of USI programs. Methods. This cross-sectional study was conducted among school-aged children (6–12 years) from randomly selected schools in the central and northern part of the Ashanti region, Kumasi Metropolis, and Ejura-Sekyedumase Municipality, respectively. A total of 852 children were enrolled in the study. Thyroid volume and urinary iodine concentrations of the children were determined using the standardized methods recommended by WHO/ICCIDD. Anthropometric measurements were also evaluated. Results. The mean values of thyroid volume in female and male school-aged children were 3.53 ± 0.09 and 3.32 ± 0.07, respectively. The thyroid size was significantly associated with age (P<0.0001), weight (P<0.0001), height (P<0.0001), BMI (P<0.05), and BSA (P<0.0001) by Pearson’s correlation in both males and females. The P50 (median) thyroid volumes of school children investigated in this study were generally larger compared to the WHO/ICCIDD reference data by age and body surface area. The median value of urinary iodine concentration was 201.85 μg/L, which showed significant sex difference (P value <0.0001). Excessive iodine nutrition (≥300 μg/L) was observed among 34.4% of male children and 27.6% of female children. Also, 12.8% of the male and 19.5% of the female children had UIC below requirement (<100 μg/L). The criteria of thyroid volume per age yielded a goitre prevalence of 2.2%. In contrast, the criteria of thyroid volume by body surface area yielded a goitre prevalence of 0.9%. Conclusion. The study clearly indicated that adequate iodine nutrition exists generally among the school children. However, insufficient and excessive iodine intakes still persist among some of the children. The establishment of local reference values for thyroid volume that might be applicable to precisely define goitre prevalence in the Ghanaian context is highly recommended.